The Experience of Visual Expression of National Traditions and Historical Heritage in Schoolchildren’s Visual Arts Lessons - Usmonova Ruxshona Feruz qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article examines the experience of visually representing national traditions and historical heritage in schoolchildren’s visual arts lessons. It emphasizes pedagogical strategies that integrate cultural content, historical knowledge, and artistic techniques to enhance students’ creativity, aesthetic perception, and cultural awareness. By exploring traditional customs, historical events, and folk symbols through drawing, painting, and other visual arts activities, students develop both technical skills and a deeper understanding of their cultural roots. The study provides practical recommendations for lesson design, interactive activities, and creative projects that encourage students to express historical and cultural themes visually.